p85β regulates autophagic degradation of AXL to activate oncogenic signaling - Ling Rao (Nature Portfolio, 2020)
p85β (PIK3R2), a regulatory subunit of PI3K, has oncogenic properties. Here the authors show that p85β promotes AXL protein stability, which in turn activates p110 to induce PDK1/SGK3 signaling, and therapeutically, p85β-expressing ovarian cancer cells are sensitive to AXL inhibition.